2019
DOI: 10.1103/physrevb.99.094107
|View full text |Cite
|
Sign up to set email alerts
|

First-principles characterization of reversible martensitic transformations

Abstract: Reversible martensitic transformations (MTs) are the origin of many fascinating phenomena, including the famous shape memory effect. In this work, we present a fully ab initio procedure to characterize MTs in alloys and to assess their reversibility. Specifically, we employ ab initio molecular dynamics data to parametrize a Landau expansion for the free energy of the MT. This analytical expansion makes it possible to determine the stability of the high-and low-temperature phases, to obtain the Ehrenfest order … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…To determine the region in the (c Ta , c X ) space where the transformation temperatures are higher than 100 • C, we have calculated the 0 K energy difference between the β and α phases ∆E (β−α ) (c Ta , c X ). In Ti-Ta based alloys, the entropy difference between the two phases depends very weakly on c Ta and c X 32 and can be assumed to be constant. Therefore, the 0 K energy difference is usually sufficient to estimate the much more computationally expensive free energy difference between austenite and martensite.…”
Section: Transformation Temperaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the region in the (c Ta , c X ) space where the transformation temperatures are higher than 100 • C, we have calculated the 0 K energy difference between the β and α phases ∆E (β−α ) (c Ta , c X ). In Ti-Ta based alloys, the entropy difference between the two phases depends very weakly on c Ta and c X 32 and can be assumed to be constant. Therefore, the 0 K energy difference is usually sufficient to estimate the much more computationally expensive free energy difference between austenite and martensite.…”
Section: Transformation Temperaturesmentioning
confidence: 99%
“…A possible alternative to Ni-Ti as high-temperature shape memory alloys (HTSMAs) 14,15 are Ti-Ta alloys [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] . In these alloys, the transformation temperatures A s and M s increase with decreasing Ta concentration c Ta , and can be as high as 430 • C when c Ta is reduced to 20 at.% 30 .…”
Section: Introductionmentioning
confidence: 99%
“…A wide array of experimental (Li et al, 2013;Gutié rrez Moreno et al, 2017;Bö nisch et al, 2014;Dobromyslov & Elkin, 2006;Moffat & Larbalestier, 1988;Elmay et al, 2017;Hao et al, 2018;Kim et al, 2013) and theoretical (ab initio) (Li et al, 2019;Ferrari et al, 2019;Gutié rrez Moreno et al, 2017;Li et al, 2013) studies bear witness to the relevance of the $ 00 MT in Ti alloys. However, despite the large amount of data gathered, a unified understanding of the crystal structure of 00 across different Ti alloys has not been reached to date.…”
Section: Introductionmentioning
confidence: 99%
“…Behera et al [13] measured the enthalpy change of Ti-xTa alloys at the temperatures ranging 463 to 1257 K, and then clearly revealed that the enthalpy came mainly from the contributions of two parts: (i) one part from untransformed α and coexisting β phases, (ii) another part from the diffusional phase transformation from α phase to β phase. Furthermore, plenty of studies on TiTa alloys were also carried out by others [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%